Analisis Pengaruh Kualitas Website Terhadap Kepuasan Pengguna Berdasarkan Metode Webqual 4.0 Pada Website Hotel 88 - Prabowo, Yoedo; Sulistiowati, Sulistiowati; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
88 hotel is part of the Waringin Hospitality based in Jakarta. 88 hotel has a website located at www.hotel88.co.id ranked website which is still under the hotel ranking competitors. The Hotel's 88 therefore to improve the quality of existing website so that visitors are getting satisfied and many who make a reservation through the website. But so far the Hotel 88 not yet knowing the flaws the website so that the Hotel 88 requires the evaluation of materials so that the quality and the satisfaction of users of the website is increased. Based on these problems then the author makes a research with the aim to analyse the influence of the quality of the website user satisfaction against 88 Hotel website based on the method of webqual 4.0. This research using a sample of as many as 100 people. Menggunakafn questionnaire data collection techniques are disseminated online or paper questionnaires to hotel guests who make a reservation through the Hotel website is 88. Data analysis using multiple linear regression. The quality of the website consists of a user's quality, quality of information, and the quality of the interaction. Results showed that (1) use of the influential quality significantly to 88 Hotel website user satisfaction, (2) quality of information user satisfaction significantly to influential website Hotel 88, and (3) the quality of the interaction effect significantly to 88 Hotel website user satisfaction. So Hotels should improve the quality of the use of the 88, the quality of information and the quality of interaction in order to increase the satisfaction of website users.